Syntactic processing tools in the classification of linguistic corpus in the work of Sibawayh - tiguercha, fazia (El Omda in Linguistics and Discourse Analysis, 2024)
Abstract : The research aims to address Sibawayh’s description of Arab words and his classification of linguistic blogs up to linguistic reticence, and among these tools is the principle of equivalence to collect isotopes in one chapter by virtue of their flowing into the course of the origin, by contrasting the linguistic blogs that he analyzed with their contradictions from hypothetical examples that do not run the course. The research reached a set of results, the most important of which is that the grammatical processing tools in the classification of the linguistic code of Sibawayh are related to the external context that carries the course of the communicative act, and the intention of the speaker.